LONG-TERM CONSEQUENCES OF CHILDHOOD AND ADOLESCENT OBESITY ON PHYSICAL AND MENTAL HEALTH: IMPLICATIONS FOR ADULT LIFE. IMPORTANCE OF PREVENTION - Natalia Pacocha,; Jakub Jędrychowski,; Natalia Karpowicz,; Małgorzata Krzyżanowska,; Marta Zgierska,; Julia Kaszucka,; Agnieszka Raczyńska,; Kinga Kosiec,; Oliwia Krzemień,; Iga Kwiecień, (International Journal of Innovative Technologies in Social Science, 2024)
Obesity among children and adolescents has become a global problem. In recent years, the number of children with excess body weight has increased. Obesity among children often persists into adulthood, consequently contributing remarkably to an increase in the incidence of many diseases. The aim of this study is to conduct a comprehensive review of literature on obesity among adults and adolescents, focused on identifying the major side effects of childhood obesity on future adult life and importance of prevention. A review of the literature available in the “PubMed” database and books was conducted. Childhood obesity may have a significant impact not only on its side effects in the early age, but may also increase the risk of developing many chronic diseases in the future. It has been shown that childhood obesity may have an important impact on the development of cardiovascular, metabolic, oncological and mental health diseases. These diseases usually do not appear at a young age, but the processes leading to their development may be initiated already in the early years of life. Due to numerous unfortunate implications in both childhood and adult life, it is crucial to prevent obesity from an early age of life, which will subsequently help to avoid many diseases in the future. Teaching children and adolescents appropriate lifestyle habits, such as healthy diet and physical activity, is very important. In order to effectively avoid the complications of obesity, new strategies and solutions should be sought to help and protect children against this serious disease.